2013
DOI: 10.1007/s00268-013-1964-2
|View full text |Cite
|
Sign up to set email alerts
|

Trauma‐related Preventable Deaths in Berlin 2010: Need to Change Prehospital Management Strategies and Trauma Management Education

Abstract: The trauma mortality in Berlin, compared to worldwide published data, is low. Nevertheless, 15.2 % (n = 40) of traumatic deaths were classified as preventable. Compulsory training in trauma management might further reduce trauma-related mortality. The main focus should remain on prevention programs, as the majority of the fatalities occurred as a result of non-survivable injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
36

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(108 citation statements)
references
References 54 publications
(44 reference statements)
4
68
0
36
Order By: Relevance
“…It could be mediated by the restriction of arterial tree and the effect of circulating catecholamines and has a potential of harm to myocardial perfusion and respiratory function, besides a raised intracranial pressure. This last issue is of particular importance, since many candidates for REBOA sustain a brain injury (9)(10)(11). Thus, redistribution of the excess of output in the areas proximal to the balloon while some degree of distal perfusion is maintained is of paramount importance.…”
Section: Physiological Effects Of the Aortic Occlusion: Proximal And mentioning
confidence: 99%
See 2 more Smart Citations
“…It could be mediated by the restriction of arterial tree and the effect of circulating catecholamines and has a potential of harm to myocardial perfusion and respiratory function, besides a raised intracranial pressure. This last issue is of particular importance, since many candidates for REBOA sustain a brain injury (9)(10)(11). Thus, redistribution of the excess of output in the areas proximal to the balloon while some degree of distal perfusion is maintained is of paramount importance.…”
Section: Physiological Effects Of the Aortic Occlusion: Proximal And mentioning
confidence: 99%
“…Most of deaths in trauma patients take place in the prehospital setting (7)(8)(9)(10). They are usually related to hemorrhage and could be preventable, which raises the question of deploying REBOA in the pre hospital setting (42,43).…”
Section: Outcomes Features and Keys For Successmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was not designed to demonstrate whether any deaths could have been prevented by faster access to EMS. However, the proportion of deaths judged to have been preventable has varied from 7 to 15% in different studies, indicating how early recognition of severely injured patients, and appropriate therapeutic interventions are important components in pre‐hospital trauma care 32, 33…”
Section: Discussionmentioning
confidence: 99%
“…In a review of twenty-four studies by Settervall et al, [14] mean preventability rate has been reported as 10.7%. In a study by Kleber et al [15] of two hundred and sixty-four traumatic deaths, the reported rates have been 5.3% preventable, 9.9% potentially preventable, and 84.8% non-preventable. Saltzherr et al [16] have evaluated forty-four cases of traumatic death in a Level 1 trauma centre and stated that one case was preventable and five cases were potentially preventable.…”
Section: Distribution According To Place and Time Of Deathmentioning
confidence: 99%